2014
DOI: 10.1039/c4sc01361a
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the structure–immunogenicity relationship of anti-Candidaglycoconjugate vaccines

Abstract: Elucidation of the molecular immunity of glycoconjugate vaccines has focused on the carbohydrate moiety, herein the effect of the corresponding conjugation sites is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…This can remarkably reduce the number of synthetic and purification steps as compared to the reported methods. [8b, 15] Three complex β-glucan oligosaccharides with β-1,3- and β-1,6-oligoglucose branches were efficiently assembled by the new strategy. It was further observed that the structure and the size of glycosyl donors and acceptors employed for preactivation-based glycosylation had little influence on the reaction efficiency, suggesting that this synthetic strategy may be broadly useful for constructing more complex oligosaccharides with good yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can remarkably reduce the number of synthetic and purification steps as compared to the reported methods. [8b, 15] Three complex β-glucan oligosaccharides with β-1,3- and β-1,6-oligoglucose branches were efficiently assembled by the new strategy. It was further observed that the structure and the size of glycosyl donors and acceptors employed for preactivation-based glycosylation had little influence on the reaction efficiency, suggesting that this synthetic strategy may be broadly useful for constructing more complex oligosaccharides with good yields.…”
Section: Resultsmentioning
confidence: 99%
“…[6] It has also been shown that β-glucans could induce strong immune responses [4] and that a vaccine composed of natural β-glucans could engender effective protection against Candida albican and Aspergillus fumigatus infections in mouse. [7] In addition, the CRM 197 protein conjugates of β-glucan oligosaccharides have been revealed to elicit immune responses comparable to that induced by the conjugates of natural β-glucans, [8] demonstrating that the oligosaccharide analogs of natural β-glucans are useful for antifungal vaccine development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive investigations of this notion in the past decade have stimulated considerable activity in the synthesis of β-(1 → 3)-glucan-related oligosaccharides and demonstrated that conjugates of either natural β-(1 → 3)-glucans from different sources (Torosantucci et al, 2005;Bromuro et al, 2010) or synthetic β-(1 → 3)linked oligoglucosides (Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) with carrier proteins are immunogenic (Torosantucci et al, 2005;Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) and protective (Torosantucci et al, 2005;Bromuro et al, 2010;Liao et al, 2015) in mice against infections induced by C. albicans and Aspergillus fumigatus. Extensive investigations of this notion in the past decade have stimulated considerable activity in the synthesis of β-(1 → 3)-glucan-related oligosaccharides and demonstrated that conjugates of either natural β-(1 → 3)-glucans from different sources (Torosantucci et al, 2005;Bromuro et al, 2010) or synthetic β-(1 → 3)linked oligoglucosides (Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) with carrier proteins are immunogenic (Torosantucci et al, 2005;Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) and protective (Torosantucci et al, 2005;Bromuro et al, 2010;Liao et al, 2015) in mice against infections induced by C. albicans and A...…”
Section: Introductionmentioning
confidence: 99%
“…The overall presence of β-(1 → 3)-glucan, pan-fungal antigen in the cell wall of all human pathogenic fungi makes this glycopolymer a rational target for the development of vaccines capable of protecting against multiple fungal pathogens. Extensive investigations of this notion in the past decade have stimulated considerable activity in the synthesis of β-(1 → 3)-glucan-related oligosaccharides and demonstrated that conjugates of either natural β-(1 → 3)-glucans from different sources (Torosantucci et al, 2005;Bromuro et al, 2010) or synthetic β-(1 → 3)linked oligoglucosides (Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) with carrier proteins are immunogenic (Torosantucci et al, 2005;Bromuro et al, 2010;Adamo et al, 2011;Hu et al, 2013;Adamo et al, 2014;Liao et al, 2015) and protective (Torosantucci et al, 2005;Bromuro et al, 2010;Liao et al, 2015) in mice against infections induced by C. albicans and Aspergillus fumigatus. Moreover, tested forms of Saccharomyces cerevisiae glucan, i.e.…”
Section: Introductionmentioning
confidence: 99%